Plan de negocios para la elaboración y comercialización de cocteles a base de licores ecuatorianos - Jara Dávila, María Belén (2015)
This project aims to integrate commercialization and localization through developing cocktails with traditional Ecuadorian liquors. Cocktails are drinks based on different liquors. Thus, these products can consist of one or more varieties of liquor, supplemented with fruits, creams, syrups, and others. Although its existence dates back to several decades ago, cocktails have never been as popular as they are today. In Ecuador, the consumption of alcoholic beverages is present in many social events. Henceforth, there is a ready market for the introduction of this product. It should be especially well-received by middle and upper class consumers.